Christian persecution, martyrdom, and orthodoxy - De Ste. Croix, Geoffrey E. M. (Oxford University Press, 2006)
Aspects of the 'Great' persecution -- The Fourth Edict in the West and the date of the Council of Elvira -- Why were the early Christians persecuted? -- Voluntary martyrdom in the early church -- Heresy, schism, and persecution in the later Roman Empire -- The Council of Chalcedon / with additions by Michael Whitby -- Early Christian attitudes to property and slavery